3D reconstruction of fruit shape based on vision and edge sections - Nasr Ali, Nasr Abdalmanan; Kamarudin, Kamarulzaman; Chee, Kiang Lam; Muhamad Azmi, Muhamad Safwan; Ismail, Abdul Halim; Abdul Rahim, Norasmadi; Wan Yahya, Wan Mohd Nooriman; Goh, Kheng Sneah; Moey, Lip Seng; Teoh, Phaik Hai; Ong, Thean Lye; Noor Hasnan, Noor Zafira (bilingual publishing, 2022)
The fruit industry has been known as one of the largest businesses in Malaysia, where most of the fruits pass through the peeling process well in advance before the final product as juice in a bottle or slices in a can. The current industrial fruit peeling techniques are passive and inefficient by cutting parts of the pulp of the fruit with peels leading to losses. To avoid this issue, a multi-axis CNC fruit peeler can be used to precisely peel the outer layer with the guidance of a 3D virtual model of fruit. In this work, a new cost-effective method of 3D image reconstruction was developed to convert 36 fruit images captured by a normal RGB camera to a 3D model by capturing a single image every 10 degrees of fruit rotation along a fixed axis. The point cloud data extracted with edge detection were passed to Blender 3D software for meshing in different approaches. The vertical link frame meshing method developed in this research proved a qualitative similarity between the output result and the scanned fruit in a processing time of less than 50 seconds.